Kejahatan Main Hakim Sendiri (Eigenrichting) Menurut Hukum Positif Dan Fiqh Jinayah - Sumardi Efendi (IAIN Langsa, 2020)
Eigenrichting itself is a crime that can cause harm to the offender as a result of his own actions, this action arises due to mistrust and distrust of law enforcement and the law itself is confronted by the public. On the other hand, as a result of these actions resulted in the emergence of victims, herein lies the problem to be investigated in this study of how eigenrichting acts which initially as a form of public response from crime turn themselves into criminals. This type of research is the Library Research, with the nature of analytic-comparative research with a juridical-normative approach. From the results of the study it was concluded that in positive law perpetrators of eigenrichting crimes can be charged under article 170 of the Criminal Code, regulating legal sanctions for perpetrators of violence against people or goods in public while in fiqh the jinayah is known as al-tawfuq where several people who commit a crime together without prior agreement because of the psychological influence and thoughts that come suddenly and the given uqubat will also be dropped according to their respective roles.